Order Creation and Communication in Healthcare - Gorman, P. N.; Lavelle, M. B.; Ash, J. S. (Methods of Information in Medicine, 2003)
Objectives: The aim of this paper is to examine the adequacy of the concept of Physician Order Entry (POE) as a model for clinical systems, and to suggest an alternative understanding of the order creation and communication process.Methods: The study is based on an interpretative analysis of POE as a model for clinical systems and the results of our recent fieldwork.Results: Observations from our recent fieldwork suggest that orders, like patient care in general, emerge from interactions among patients, physicians, nurses, family members, and others, employing a variety of technologies and information resources in the process. Orders as we have observed them originate, are negotiated, and are carried out in a dynamically evolving group with fluctuating membership and shifting role responsibilities. Furthermore, orders by themselves represent only a partial picture of what is done for the patient.Conclusion: We argue that information systems are more likely to be helpful if they accommodate and facilitate POE as a multidisciplinary collaboration effort and fit better into the larger system of patient care.
Keywords: Computerized physician order entry (CPOE); human computer interaction; social informatics; distributed cognition